2011
DOI: 10.1175/2010jcli3833.1
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Boreal Summer Intraseasonal Oscillations and Synoptic-Scale Disturbances over the Western North Pacific. Part I: Energetics Diagnosis*

Abstract: The role of scale interactions in the maintenance of eddy kinetic energy (EKE) during the extreme phases of the intraseasonal oscillation (ISO) is examined through the construction of a new eddy energetics diagnostic tool that separates the effects of ISO and a low-frequency background state (LFBS; with periods longer than 90 days). The LFBS always contributes positively toward the EKE in the boreal summer, regardless of the ISO phases. The synoptic eddies extract energy from the ISO during the ISO active phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 33 publications
4
79
0
Order By: Relevance
“…Dissipation is represented by the last term. Equation (1) describes the energetic budget terms between the mean state and perturbations and is different from that in Hsu et al (2011) because they included terms that involve vertical fluxes and eddy-eddy interaction terms that are from the perturbation advection term. According to Mu and Zhang (2008), these terms are small (though they are non-zeroes) and the present study focuses on the interaction between the mean state and perturbations.…”
Section: Data and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Dissipation is represented by the last term. Equation (1) describes the energetic budget terms between the mean state and perturbations and is different from that in Hsu et al (2011) because they included terms that involve vertical fluxes and eddy-eddy interaction terms that are from the perturbation advection term. According to Mu and Zhang (2008), these terms are small (though they are non-zeroes) and the present study focuses on the interaction between the mean state and perturbations.…”
Section: Data and Proceduresmentioning
confidence: 99%
“…The definitions of other terms render them unsuitable for examining the interaction between the TSM and ISO components (Hsu et al 2011), and were thus ignored. This study focused on the kp si term to delineate the interaction between the TSM and ISO.…”
Section: Data and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The oscillation was also shown to be of a more broadband pattern (20-90 days) than the original 40-50-day period (e.g., Krishnamurti and Subrahmanyam 1982;Wang and Rui 1990;Hendon and Salby 1994;Annamalai and Slingo 2001;Zhang 2005). Recent theoretical and diagnostic studies indicated that equatorial waves interacting with moisture, convection, and boundary layer dynamics build the fundamental mechanism for the eastward propagation of the MJO (Hsu and Li 2012;Sobel and Maloney 2013;Jiang et al 2015;Wang et al 2016;Wang et al 2017 mostly takes place over the western equatorial Indian Ocean (Zhang and Ling 2017) and is caused by anomalous low-level moisture advection (Zhao et al 2013), warm advection-induced anomalous ascending motion (Li et al 2015), intraseasonal SST anomalies (Li et al 2008), and/or extratropical forcing (Hsu et al 1990;Zhao et al 2013). Li (2014) provides a comprehensive review on the dynamics of MJO initiation and propagation.…”
mentioning
confidence: 99%
“…The TD-type disturbances may be enhanced under an active ISO phase due to barotropic energy conversion that involves both the rotational and divergent components of ISO wind (e.g. Hsu et al, 2011). The atmospheric ISO consists of two dominant modes of quasi-biweekly oscillation (QBW) and Madden-Julian oscillation (MJO) (e.g.…”
Section: Introductionmentioning
confidence: 99%